2004
DOI: 10.1016/j.meatsci.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Proteome changes during pork meat ageing following use of two different pre-slaughter handling procedures

Abstract: The influence of postmortem storage time and pre-slaughter conditions (transport the day before slaughter or immediately before slaughter) on proteome changes of pork meat was investigated over a 72 h ageing period. Intensities of 37 spots varied significantly (p<0.05) with ageing time. Changes indicated proteolysis of troponin T, actin, α-crystallin, myokinase, creatine kinase and mitochondrial ATPase, but also of proteins constitutive of the Z-lines, namely cypher proteins and myozenin. Other modifications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 39 publications
5
78
1
3
Order By: Relevance
“…Post-mortem proteolysis of troponin T by calpains was confi rmed by coherent spot patt ern changes of simultaneously decreasing full-length protein spots and an increasing fragment spot. The present study is in agreement with the previously reported proteolysis patt ern of TnT in beef and pork (5,10,14). Bjarnadόtt ir et al (3) reported that in bovine LT muscle sTnT isoform was more abundant 48 h post-mortem, while fTnT isoform was less abundant.…”
Section: Troponin Tsupporting
confidence: 93%
“…Post-mortem proteolysis of troponin T by calpains was confi rmed by coherent spot patt ern changes of simultaneously decreasing full-length protein spots and an increasing fragment spot. The present study is in agreement with the previously reported proteolysis patt ern of TnT in beef and pork (5,10,14). Bjarnadόtt ir et al (3) reported that in bovine LT muscle sTnT isoform was more abundant 48 h post-mortem, while fTnT isoform was less abundant.…”
Section: Troponin Tsupporting
confidence: 93%
“…Laville et al (2005) also reported the appearance of 31 and 34 kDa protein fragments in stored pig muscle (4°C for 72 h), suggesting that these fragments correspond to products of CK proteolysis. Similar results were reported by Morzel et al (2004). During ageing of bovine muscle (4°C for up to 15 days), one peptide (~5.7 kDa) was isolated and identifi ed as a product of CK proteolysis (Stoeva et al, 2000).…”
Section: Creatine Kinase and Meat Qualitysupporting
confidence: 84%
“…Proteins which were differentially expressed at two-fold differences were excised, purified and sequenced using MALDI TOF/TOF analysis according to the manufacturer's protocol (Morzel et al, 2004). The resultant peptide sequences were compared to the ones in the database (http://www.matrixscience.com/cgi/).…”
Section: Protein Expression and Identificationmentioning
confidence: 99%
“…Proteomics offers platform for understanding the biochemical basis of meat quality in relation to postmortem muscle metabolism and pre-slaughter handlings (Amid, Samah, & Yusof, 2012;Morzel et al, 2004). Thus, the present study was carried out to examine and compare the effects of gas stun-to-kill prior to neck cut and slaughtering without stunning (Halal slaughter) on quality traits and proteome profile of breast muscles in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%